Complications of spinal and general anesthesia for total knee arthroplasty - S. A. Abdulahad; H. M. Mohammad; B. K. Abd-Al-Qader (Амбулаторная хирургия)
Introduction. General anesthesia (GA) and spinal anesthesia (SA) are the main techniques applied during total knee arthroplasty (TKA). SA belongs to neuraxial anesthesia (NA) category. Numerous studies have explored benefits of NA in diminishing the complications, among which are pulmonary embolism (PE), urinary tract infection (UTI), and deep vein thrombosis (DVT). Aim. To compare rate of complications of SA and GA in TKA. Materials and methods. This is a retrospective cohort studie conducted on 190 patients who attended Alwasity teaching hospital in Baghdad and underwent TKA. The age ranged from 41 to 75 years and 69% of patients were females. The patients were enrolled into SA group (80 patients) and GA group (110 patients). We reviewed patients’ records and interviewed patients and medically examined them to obtain data on age, sex, body mass index (BMI), comorbidities including diabetes mellitus(DM), hypertension (HT) and other comorbidities. Results: Higher age and BMI were found in SA group. Complications’ incidence in SA group vs. GA group was PE 0.03 vs. 0.09, DVT 0.04 vs. 0.10, Pneumonia 0.04 vs. 0.08, UTI 0.06 vs. 0.23, and ARF 0.03 vs. 0.33, they didn’t differ significantly. Conclusion: SA is a good option for anesthesia in TKA because it wasn’t associated with higher complications rate compared to GA.